Ambivalence and motivational interviewing with adolescents: ensuring that the baby does not get thrown out with the bathwater. (30th March 2016) - Monti, Peter M.; Monnig, Mollie
Abstract : Commentary to:Ambivalence: Prerequisite for success in motivational interviewing with adolescents?